Antimicrobial activity of chitosan /corn starch film incorporated with starch nanocrystals /nettle essential oil nanoemulsion for Eleutheronema tetradactylum fillet preservation - Hamed Ahari; Fatemeh Kalateh-Seifari; Shima Yousefi (Food Chemistry: X)
This study aimed to estimate the effects of chitosan/ corn starch (CH/ CS equal 62:38) film in combination with nettle essential oil nanoemulsions (0.41 wt% NEONEs) and starch nanocrystals (6 wt% SNCs) on the microbial and qualitative characteristics of the Eleutheronema tetradactylumfillets during refrigeration storage (4 ± 1 °C). The fillets were covered by biopolymeric films (CH/CS, CH/CS/SNCs, CH/CS/ NEONEs, CH/CS/SNCs/NEONEs). The qualitative analysis of refrigerated fillets was performed on days 1, 7, and 10. The incorporation of NEONEs and SNCs into CH/CS made an active film with antimicrobial effects. The decrease in pH (5.89 %), PV (44.72 %), FFA (10.41 %), TVB-N (35.01 %), TBA (27.07 %) and increase in moisture (5.38 %) were observed in the covered fillets by CH/CS/SNCs/NEONEs film in compared to uncovered fillets at 4 °C on day 10. The results revealed that incorporating SNCs (6 %) and NEONEs (0.41 %) into CH/CS could increase the storage time of the refrigerated fish fillets.